Peran Negara dalam Menjamin Kebebasan Berekspresi Menurut Konstitusi dan Hukum HAM - Natamiharja, Rudi (Penerbit Goodwood, 2025)
Purpose: This study aims to critically analyze the role of the Indonesian state in guaranteeing freedom of expression as a constitutional and human right while examining the legal challenges and restrictions that hinder its implementation. Methodology/approach: This research applies a normative legal method using a conceptual and statutory approach. This study is based on legal instruments such as the 1945 Constitution of the Republic of Indonesia, the Electronic Information and Transactions Law (ITE Law), the revised Criminal Code (KUHP), and international human rights standards, particularly the ICCPR. Relevant judicial decisions and academic legal doctrines were reviewed. Results/findings: The findings indicate a normative gap between the constitutional guarantee of freedom of expression and the repressive implementation of sectoral regulations. Laws such as the ITE Law and the Criminal Code are frequently misused to criminalize criticism, especially on digital platforms, thus undermining democratic principles. Conclutions: The state plays a dual roleas both protector and limiter of freedom of expression. However, an imbalance in the exercise of these roles has led to systematic human rights violations. Legal harmonization and stricter adherence to international standards are urgently required. Limitations: This study is limited to normative analysis and does not include empirical data or case studies involving victims of expression-related repression. Contribution: This study contributes to the legal scholarship on constitutional rights, particularly in the field of freedom of expression and democratic governance. It may benefit researchers, legal reform advocates, policymakers, and human rights institutions concerned with freedom of speech in Indonesia and other democratic legal systems.